Precision performance evaluation of RTK and RTN solutions: a case study. Issue 3 (2nd September 2022) - Mora, Omar E.; Langford, Matthew; Mislang, Rudy; Josenhans, Richard; Chen, Jorge
ABSTRACT: Throughout the past few decades, advancements in global navigation satellite systems (GNSS), such as the Global Positioning System (GPS), have resulted in real-time planimetric accuracy at the centimetre level, whether achieved using Real-Time Kinematic (RTK) or Real-Time Network (RTN) approaches. This study examines and characterizes the performance of RTK and RTN solutions at three test sites in Los Angeles County, California, in the United States of America. The solutions were characterized to examine the dispersion of vertical measurements in the context of different environments. The results from this study suggest that both methods have advantages and drawbacks; in particular, the data showed that the distribution and density of the network stations, cellular network coverage and environmental dynamics have significant impacts on RTN vertical precision, where the vertical precision for the RTN measurements were observed to be 2–4 times lower in comparison to the RTK measurements.